2012
DOI: 10.4028/www.scientific.net/amr.486.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment Temperature of Electrospun PET Nanofiber Mat on Tensile Properties

Abstract: The electrospinning technique was used to prepare the Polyethylene Terephthalate (PET) mats. The electrospun PET mats with different fiber diameters have many applications such as biotechnological and biomedical, functional coating, lithum-ion membrane and filtering membrane and so on. Several techniques including scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and single fiber electronic tensile strength tester were used to characterize the electrospun PET mats before/after thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Both increased the mechanical strength. Meanwhile, elongation at break was decreased for PET-T, which was consistent with other works . These results indicated that PET exhibited brittle behavior after thermal treatment.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Both increased the mechanical strength. Meanwhile, elongation at break was decreased for PET-T, which was consistent with other works . These results indicated that PET exhibited brittle behavior after thermal treatment.…”
Section: Resultssupporting
confidence: 90%
“…This finding showed that heat treatment increased the tensile strength of PET was similar to the results reported by other researchers. 43 According to the results of DSC and XRD, the high temperature in the process of heat treatment and autoclaving fused the crystalline and amorphous regions of the PET, making the crystallization more perfect, which may largely contribute to the increase in Young's modulus and tensile strength. The research of Cho et al 44 found that PET molecules in PET fibers were relaxed and crystallized to some extent during heat treatment.…”
Section: Characterization Of Pet Sponge After Thermalmentioning
confidence: 99%